Comparative Analysis of Stylistic Devices in English and Uzbek Literary Texts - Rakhimboeva , Mashkhura (Zamonaviy ilmiy yondashuvlar va texnologik taraqqiyotning ustuvor yo‘nalishlari, 2026)
Stylistic devices are integral to literary texts, allowing authors to convey nuanced emotions, create aesthetic appeal, and reflect cultural identity. This study examines the comparative use of stylistic devices in English and Uzbek literature, focusing on metaphor, simile, hyperbole, imagery, sound devices, irony, and humor. By analyzing selected works of William Shakespeare, Jane Austen, Abdulla Qodiriy, and Cho‘lpon, the research highlights universal and culture-specific tendencies. Findings indicate that English literature favors conciseness, abstraction, and subtle stylistic effects, while Uzbek literature emphasizes elaboration, emotional resonance, and culturally embedded symbolism. The study also addresses implications for translation, providing guidance for preserving stylistic and cultural nuances across languages.